Facile and Sustainable Synthesis of Commendamide and its Analogues - Villano, Rosaria; Tinto, Francesco; Di Marzo, Vincenzo (Frontiers in Chemistry, 2022)
Commendamide, or N-(3-hydroxypalmitoyl)-glycine 1a, is a gut microbiota-derived bioactive metabolite, structurally similar to long-chain N-acyl-amino acids which belong to the complex lipid signaling system known as endocannabinoidome and play important roles in mammals through activation of, inter alia, G-protein-coupled receptors (GPCRs). In this work, we describe a simple, green and economic method for the preparation of commendamide 1a, a GPCR G2A/132 agonist. The developed protocol is general and could also be applied to the synthesis of deuterated commendamide 1b, as well as to other minor microbiota-derived metabolites, such as the analog 2.